1987
DOI: 10.1080/00332747.1987.11024346
|View full text |Cite
|
Sign up to set email alerts
|

Identity and Individuality in the Nouveau-Religious Patient

Abstract: Revitalized interest in the clinical complexities of psychotherapy with religious patients (for example, Bradford 1984; Lovinger 1984; Spero 1985a; Stern 1985) has drawn attention to the need for perspectives on religious personality development that account for healthy and adaptational aspects as well as psychopathological aspects of particular forms and levels of religious beliefs, enabling more creative, enriching psychotherapy. This search represents movement beyond the significance of infantile wish-fulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A "transitional theory" has also been proposed to account for the development of religious faith. Transition can refer to crises (Hall, 1986), identity issues (Spero, 1987), or coping strategies (Pargament, 1987). Cognitive attribution theory is also seen as relevant to the life-transitions model of religious development.…”
Section: Developmental Aspects Of Religion and Mental Healthmentioning
confidence: 99%
“…A "transitional theory" has also been proposed to account for the development of religious faith. Transition can refer to crises (Hall, 1986), identity issues (Spero, 1987), or coping strategies (Pargament, 1987). Cognitive attribution theory is also seen as relevant to the life-transitions model of religious development.…”
Section: Developmental Aspects Of Religion and Mental Healthmentioning
confidence: 99%
“…For example, studies have investigated religious practice from the perspective of Piaget's theory of cognitive development both in children (Elkind, 1964;Long, Elkind, & Spilka, 1967) and in adolescents (Allport, Gillespie, & Young, 1948;Goldman, 1964;Pealting, 1974). Other studies have examined the relationship between religion and moral development (Bull, 1969;Clouse, 1978), Erikson's theory of psychosocial development in children (Steele, 1986) and in adults (Whitehead & Whitehead, 1979), and transition theory (Hall, 1986;Spero, 1987). Although these authors have not concluded that religious development is a necessary part of psychological development, research over the years has established a connection between these two dimensions for those who profess religious belief.…”
mentioning
confidence: 99%
“…The social work values of acceptance and respect for cultural diversity and client self-determination support a spiritually-sensitive client-centered value framework for the assessment of religious groups. Several authors (Canda, 1990;Loewenberg, 1988;Spero, 1987;Siporin, 1990) have commented on the importance of reflecting on the impact that a practitioner's own values may have on the evaluation of clients' religious or spiritual concerns. A non-religious practitioner may tend to underestimate the importance of the spiritual or religious dimension for the client, and the sectarian or anti-religious practitioner must be cautious about being judgmental toward belief systems that seem foreign.…”
Section: Review Of the Literaturementioning
confidence: 98%